A rare cause of Hemiplegia - Renuji, Baishyak; Jose, Joby; Ajith, Karthika; Eldho, Avin (Nepal Journal of Neuroscience, 2023)
Stroke is the most likely diagnosis considered, when an elderly patient comes to ER with acute onset hemiplegic weakness. Here we report a case of 82-year-old male, known diabetic and hypertensive with complaints of weakness of left upper limb and lower limb since one day. His MRI brain was normal and MRI cervical spine screening showed epidural hematoma which was later evacuated resulting in improvement of symptoms. SSEH is a rare entity, its presentation as hemiplegia is very rare and has not been reported previously. Keeping SSEH as a possibility in MRI brain negative patient presenting with hemiplegia can be beneficial to the patient as early surgical intervention will provide a good outcome.